(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
Chronic aphthous stomatitis (CAS) is a recurrent, painful ulcerative condition of the oral mucosa, significantly affecting the quality of life. In women of reproductive age, hormonal fluctuations, nutritional deficiencies, and immune modulation can influence the course and severity of the disease. Despite the widespread prevalence, the pathogenesis and optimal management of CAS in this demographic group remain under-researched. This study aims to elucidate the clinical peculiarities of CAS in reproductive-aged women and improve therapeutic approaches based on individualized patient factors.